Etched in flesh and soul : the Auschwitz number in art - Bruṭin, Batyah 1949- (De Gruyter, 2021)
A series of numbers was tattooed on prisoners’ forearms only at one location - the Auschwitz concentration camp complex. Children, parents, grandparents, mostly Jews but also a significant number of non-Jews scarred for life. Indelibly etched with a number into their flesh and souls, constantly reminding them of the horrors of the Holocaust. References to the Auschwitz number appear in artworks from the Holocaust period and onwards, by survivors and non-survivor artists, and Jewish and non-Jewish artists. These artists refer to the number from Auschwitz to portray the Holocaust and its meaning. This book analyzes the place that the image of the Auschwitz number occupies in the artist’s consciousness and how it is grasped in the collective perception of different societies. It discusses how the Auschwitz number is used in public and private Holocaust commemoration. Additionally, the book describes the use of the Auschwitz number as a Holocaust icon to protest, warn, and fight against Holocaust denial.